Efficacy of a dedicated plastic stent in endoscopic ultrasound-guided hepaticogastrostomy during the learning curve: cumulative multi-center experience. (4th March 2023) - Kitagawa, Koh; Mitoro, Akira; Minami, Ryuki; Nagamatsu, Shinsaku; Ozutsumi, Takahiro; Fujinaga, Yukihisa; Nishimura, Norihisa; Sawada, Yasuhiko; Namisaki, Tadashi; Akahane, Takemi; Kaji, Kosuke; Tomooka, Fumimasa; et al.
Abstract: Background and objectives: Currently, there are no reports on the learning curve of endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) using dedicated plastic stents. Therefore, we evaluated the outcomes of EUS-HGS using dedicated plastic stents at tertiary referral centers during the initial development phase of EUS-HGS. Materials and methods: Endoscopic retrograde cholangiopancreatography (ERCP) was strictly prioritized over EUS-HGS. Twenty-three consecutive patients treated using EUS-HGS with a 7-Fr dedicated plastic stent over 4 years beginning in 2018 were analyzed retrospectively. Results: The most common primary disease was pancreatic cancer, and the most common reason for difficulty in ERCP was duodenal obstruction, followed by surgically altered anatomy. The overall technical success rate of EUS-HGS was 95.7% (22/23). One failed case was converted to EUS-guided choledochoduodenostomy. The clinical success rate was 90.9% (20/22). Adverse events (AEs) related to the procedure were observed in four (17.4%) patients, including mild biliary peritonitis in three (13.0%) and mild cholangitis in one (4.3%) patient; all patients received conservative therapy. No serious AEs, such as stent migration, bleeding, or gastrointestinal perforation, were observed. Recurrent biliary obstruction (RBO) was observed in eight (34.8%) patients. Of these, HGS stent replacement was performed in four patients, and other treatments were performed in the remaining four patients. Another four (17.4%) patients did not develop RBO but underwent periodic HGS stent replacement. Conclusions: EUS-HGS using a dedicated plastic stent was performed safely even in its initial phase of introduction. The approach using this stent can be useful in case of ERCP failure for biliary decompression because of the high feasibility and low risk of serious adverse events.